A case report: successful percutaneous coronary intervention (PCI) in unprotected left main and three-vessel coronary artery disease - Kahadi, Cik; Rohman, Mohammad Saifur (Heart Science Journal, 2024)
Background: Left Main Coronary Artery (LMCA) Disease is the highest-risk lesion of coronary artery disease and is related to cardiovascular morbidity and mortality compared to other types of obstructive Coronary Arterial Disease (CAD). Previously, coronary artery bypass grafting (CABG) was the preferred method for revascularization in significant LMCA lesions; however, results from several trials comparing percutaneous coronary intervention (PCI) with drug-eluting stents (DES) to CABG showed PCI was non-inferior to CABG in highly selected LMCA patients. This report was to describe the contemporary evidence for PCI to CABG in LMCA Disease.Case Presentation: A diabetic and hypertensive 59-year-old man with stable angina pectoris and Canadian Cardiovascular Society (CCS) Score III was referred to Saiful Anwar Hospital for elective PCI consideration. The patient was diagnosed with left main and three-vessel coronary artery disease from CCTA in 2009 and angiography in 2023, then suggested to CABG for revascularization. However, the patient refused CABG surgery and decided to perform PCI with high-risk criteria after an adequate consultation. Considering the high-risk category and reduced ejection fraction, an elective PCI was performed with intra-aortic balloon pump (IABP) support. Then it implanted 2 DES at distal-LM until distal-LCx. In the following procedure, the patient also implanted 1 DES at mid-distal RCA and was discharged with significant improvement in his quality of life.Conclusion: In selected left main and three-vessel coronary artery disease, PCI is successfully improves the patient's quality of life